An unusual presentation of pyogenic granuloma of the lower lip - V Asha; M Dhanya; Bharati A Patil; G Revanna (Wolters Kluwer Medknow Publications, 2014)
Exophytic growth of the oral cavity often presents a diagnostic challenge because a diverse group of the pathologic process can produce such lesions. Inflammatory hyperplasia is one of the important etiology behind the exophytic growths of the oral cavity. The pyogenic granuloma (PG) is the most common type of inflammatory hyperplasia found in the oral cavity especially in the gingiva. Extragingival occurrence of PG is very rare. This case report has described an extragingival PG which occurred on the lower labial mucosa in a 54-year-old male patient.